Voice Condition Following Short-Term Endotracheal Intubation in Head and Neck Surgery: Study Protocol for Clinical Trial - Ivana Šimić; Renata Curić Radivojević; Juraj Slipac; Drago Prgomet (Acta Clinica Croatica, 2023)
Endotracheal intubation is an airway management procedure commonly performed under general anesthesia. It is linked with postoperative voice changes. The incidence and reasons of hoarseness and vocal cord injury are not very well investigated, especially after short-term anesthesia and intubation in head and neck surgery. The aim of the study is to identify the causes of voice changes after short endotracheal anesthesia in head and neck surgery. The study will include patients scheduled for head and neck surgery under general anesthesia with endotracheal intubation up to 3 hours. There will be 3 groups of patients, as follows: thyroid surgery, non-thyroid surgery, and control group undergoing surgery outside head and neck. Videostroboscopy will be recorded before and after surgery. Further diagnostic workup will include voice status; subjective voice self-analysis; perceptive and objective acoustic voice analysis at 4 time points (preoperatively, postoperative day 2, 2 weeks and 1 month after surgery). Endotracheal intubation is a safe method of airway management although it can temporarily alter a patient’s voice quality. It is not known how much of this is the result of anesthesia, general condition of the patient, or surgery. This trial is expected to shed some light on this issue.